2022
DOI: 10.1111/1753-6405.13160
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence education in Australian medical schools: has anything changed?

Abstract: Objectives: To describe current intimate partner violence (IPV) education delivery to Australian medical students, and the barriers influencing this delivery, including any changes in the quantity and nature of IPV education delivery since 2010. Methods:A cross-sectional analysis of Australian medical schools providing primary medical degrees was conducted by identifying one staff member, from each of the disciplines of general practice, obstetrics and gynaecology, paediatrics, and where necessary, medical edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Additional educational objectives not explicitly covered in guidance from national professional bodies Some studies identified additional educational objectives, not covered in guidance from national professional bodies. These included teaching on intimate partner violence, 31 content for Muslim patients, 27 mental health education, 32 and training requirements in low-and middle-income countries. Key differences identified by our rapid review were requirements for students to be skillful enough to perform insertion of intrauterine contraceptive devices, repair episiotomies, and perform cervical biopsies, endometrial biopsies, and colposcopy.…”
Section: Obstetrics and Gynecology Curriculum Content For Medical Stu...mentioning
confidence: 99%
“…Additional educational objectives not explicitly covered in guidance from national professional bodies Some studies identified additional educational objectives, not covered in guidance from national professional bodies. These included teaching on intimate partner violence, 31 content for Muslim patients, 27 mental health education, 32 and training requirements in low-and middle-income countries. Key differences identified by our rapid review were requirements for students to be skillful enough to perform insertion of intrauterine contraceptive devices, repair episiotomies, and perform cervical biopsies, endometrial biopsies, and colposcopy.…”
Section: Obstetrics and Gynecology Curriculum Content For Medical Stu...mentioning
confidence: 99%